2012
DOI: 10.1099/mic.0.062380-0
|View full text |Cite
|
Sign up to set email alerts
|

RpoH2 sigma factor controls the photooxidative stress response in a non-photosynthetic rhizobacterium, Azospirillum brasilense Sp7

Abstract: Bacteria belonging to the Alphaproteobacteria normally harbour multiple copies of the heat shock sigma factor (known as s 32, s H or RpoH). Azospirillum brasilense, a non-photosynthetic rhizobacterium, harbours five copies of rpoH genes, one of which is an rpoH2 homologue. The genes around the rpoH2 locus in A. brasilense show synteny with that found in rhizobia. The rpoH2 of A. brasilense was able to complement the temperature-sensitive phenotype of the Escherichia coli rpoH mutant. Inactivation of rpoH2 in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Recently, we reported that carotenoid synthesis is induced by light and regulated by a pair of ECF sigma factors (RpoE1 and RpoE2) in this bacterium (16)(17)(18). In addition, we have also shown that a heat shock sigma factor (RpoH2, or H ) is involved in the photooxidative stress response in this bacterium (19). These observations suggested that, besides RpoE1-ChrR1, RpoH2 might also be involved in the regulation of carotenoid biosynthesis in A. brasilense Sp7.…”
Section: Importancementioning
confidence: 73%
See 1 more Smart Citation
“…Recently, we reported that carotenoid synthesis is induced by light and regulated by a pair of ECF sigma factors (RpoE1 and RpoE2) in this bacterium (16)(17)(18). In addition, we have also shown that a heat shock sigma factor (RpoH2, or H ) is involved in the photooxidative stress response in this bacterium (19). These observations suggested that, besides RpoE1-ChrR1, RpoH2 might also be involved in the regulation of carotenoid biosynthesis in A. brasilense Sp7.…”
Section: Importancementioning
confidence: 73%
“…Identification of an RpoH-dependent promoter in the crtE2 upstream region prompted us to use the two-plasmid system to examine which of the five RpoH paralogs, encoded in the genome of A. brasilense (19), directly regulate crtE genes. Since the rpoH gene of E. coli is expressed under a heat shock condition, expression of ␤-galactosidase in E. coli DH5␣ can be observed only if an A. brasilense RpoH protein is able to drive the expression of lacZ from the crtE1 or crtE2 promoters.…”
Section: Resultsmentioning
confidence: 99%
“…Azospirillum strains (and more particularly A. lipoferum 4B) harbor a remarkably high number of rpoH paralogues. While most of the Alphaproteobacteria harbor two copies of genes encoding RpoH sigma factors, this gene is present in five copies in the strains A. brasilense Sp7 and A. brasilense Sp245, whereas six copies are found in the A. lipoferum 4B genome (Wisniewski‐Dyé et al ., ; Kumar et al ., ). Interestingly, two copies ( rpoH4 and rpoH6 ) are similarly induced in sessile cells associated to artificial and rice roots (see above) and one copy is induced ( rpoH1 ) only in rice‐associated cells, suggesting that rpoH alleles are finely regulated during the adaptation of A. lipoferum 4B to rice roots.…”
Section: Resultsmentioning
confidence: 97%
“…Since oxidative and photooxidative stresses often lead to the denaturation of proteins, it was hypothesized that other paralogs might be involved in coping with stresses that cause protein denaturation. We have previously shown an involvement of RpoH2 in tolerating photooxidative stress in A. brasilense (36). In this study, the inability of rpoH3::km and rpoH5::km mutants to grow at 1 mM H 2 O 2 and severalfold induction of rpoH3 and rpoH5 transcripts by 1 mM H 2 O 2 indicated that both RpoH3 and RpoH5 were involved in coping with H 2 O 2 stress.…”
Section: Discussionmentioning
confidence: 48%
“…Both of these RpoE sigma factors respond to photooxidative or oxidative stress through their cognate anti-sigma factors, which possess redox-active zinc-binding motifs (2). Earlier, we had shown for A. brasilense that carotenoid biosynthesis, which confers protection against photooxidative stress (36)(37)(38), is regulated by two cascades of sigma factors, RpoE1¡RpoH2 and RpoE2¡RpoH1 (39). The genome of A. brasilense also encodes two copies of OxyR regulators, of which one is involved in the negative regulation of AhpC (40).…”
mentioning
confidence: 99%